Modelação matemática na sala de aula: o conceito de função exponencial numa sequência de atividades para o 1º Ano do ensino médio - Maia, Lina Flávia Morete de Queirós (2017)
This academic research is intended to present a sequence of activities in order to teach the exponential function in an instinctive way, and afterwards, present its definition in an attempt to formalize the properties that will be discovered by the students. The research starts with an analysis of some specific peaces of academic documents that also presents the exponential function. Aligned with such documents we present the Mathematic Modeling proposed by Bassanezi (2004) and the assumption of the Mathematical Modeling defined by Biembengut and Hein (2016). The sequence of activities is composed by eight activities involving social daily situations, the students will then have the opportunity to discuss around such scenarios in order to reach the mathematical models required to solve the scenarios under discussion, after that, the stundents will build the graphics of curves to describre the situations, with digital spreadsheets as the tool to design the solution. In the end, we expect to also motivate the professors to use the Mathematical Modeling with real examples as more tangible teaching strategy, linking mathematic with usual daily situations for the students.